2015
DOI: 10.1002/ppsc.201500083
|View full text |Cite
|
Sign up to set email alerts
|

Oleylamine‐Assisted Phase‐Selective Synthesis of Cu2−xS Nanocrystals and the Mechanism of Phase Control

Abstract: Environmentally friendly Cu2−x S compounds exist in many different mixed phases in nature, while their nanoscale counterparts can be pure phase with interesting localized surface plasmon resonance properties. Because of the complexity of composition and phase, controllable synthesis of Cu2−x S nanocrystals becomes an important scientific issue in colloidal chemistry. In this work, a hot‐injection method is developed to synthesize Cu2−x S nanocrystals by injecting a sulfur precursor into a copper precursor usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
5
19
0
Order By: Relevance
“…Figure S5 shows the corresponding XRD patterns of the mixtures. The existence of Cu 3 BiS 3 may be due to the phase transformation of Cu 2‐x S precursor while the molar ratio of Cu/S changed with a low chemical potential of Cu 3 BiS 3 ,. Subsequently, we investigated the effect of regulating the ratios of Cu 7.2 S 4 and Bi 2 S 3 precursors.…”
Section: Resultssupporting
confidence: 68%
“…Figure S5 shows the corresponding XRD patterns of the mixtures. The existence of Cu 3 BiS 3 may be due to the phase transformation of Cu 2‐x S precursor while the molar ratio of Cu/S changed with a low chemical potential of Cu 3 BiS 3 ,. Subsequently, we investigated the effect of regulating the ratios of Cu 7.2 S 4 and Bi 2 S 3 precursors.…”
Section: Resultssupporting
confidence: 68%
“…[29][30][31][32][33][34][35][36][37][38] Here, hexagonal CuS, monoclinic Cu 1.75 S, and rhombohedral Cu 1.8 SN Cs were synthesized by ah ot-injection method;t he crystal structures of the as-synthesized CuS, Cu 1.8 S, and Cu 1.75 SN Cs have been identified by XRD and highresolution TEM in our previousw ork. [39,40] The heat-induced phase transformation of Cu 1.8 SN Cs has also been studied in Owing to their high electrical conductivity,t unable plasmonic absorption spectra, low cost, and abundancei nn ature,C u 2Àx S nanocrystalsa re of great interest as functional materials for photovoltaic and photothermal applications. With the aim of developing low-cost high-efficiency quantum-dot-sensitized solar cells, solution-processed Cu 2Àx Sn anocrystal films are synthesized and their phase transformations upon thermalt reatment are investigated.…”
Section: Resultsmentioning
confidence: 99%
“…From the Cu 2p XPS spectra shown in Figure a, it was evident that the valency of Cu in case of covellite CuS is +1. The strong satellite shakeup peaks at 942.5 and 962.1 eV that appeared in Figure b and c were attributed to the Cu 2+ oxidation state in Cu 1.39 S and Cu 2 S, respectively. This observation suggests that CuS contains only Cu + ions (monovalent state), while both Cu 1.39 S and Cu 2 S are comprised of copper ions with mixed valence states of +1 and +2 …”
Section: Figurementioning
confidence: 91%
“…In particular, the covellite CuS was reported to be in the monovalent state (Cu + ) with either [(Cu 1+ ) 3 (S 2 2− ) (S 1− )] or [(Cu 1+ ) 3 (S 2 − ) (S 2− )] structure, while other reports have suggested that Cu may be present in both Cu + and Cu 2+ states with [(Cu 2+ )(S 2 2− )(Cu + ) 2 (S 2− )] structure ,. Similarly, the intermediate Cu x S materials such as Cu 1.8 S and Cu 1.75 S could be represented as [(Cu + ) 8 Cu 2+ (S 2− ) 5 ] and [(Cu + ) 6 Cu 2+ (S 2− ) 4 ] with the atomic ratios of Cu(II):Cu(I) of 1:8 and 1:6, respectively . As observed in the present work, the composition of the final Cu x S product was mainly dependent on the sodium thiosulfate concentration, which was used for the complete reduction of Cu 2+ to Cu + for the synthesis of CuS and partial reduction in the case of the synthesis of Cu 1.39 S and Cu 2 S, as evident from Figure S1.…”
Section: Figurementioning
confidence: 99%